OVERVIEW OF C# - Rohdia, Taruna (IJRDO -Journal of Computer Science Engineering, 2015)
A type of programming in which programmers define not only the data type of a data structure, but also the types of operations (functions) that can be applied to the data structure. In this way, the data structure becomes an object that includes both data and functions. In addition, programmers can create relationships between one object and another. Object-oriented technology is becoming increasingly popular in industrial software development environments. This technology helps in the development of a software product of higher quality and lower maintenance costs. One of the principal advantages of object-oriented programming techniques over procedural programming techniques is that they enable programmers to create modules that do not need to be changed when a new type of object is added. A programmer can simply create a new object that inherits many of its features from existing objects.